Diverse novel resident Wolbachia strains in Culicine mosquitoes from Madagascar. Issue 1 (December 2018) - Jeffries, Claire; Tantely, Luciano; Raharimalala, Fara; Hurn, Eliot; Boyer, Sébastien; Walker, Thomas
Abstract Wolbachia endosymbiotic bacteria are widespread throughout insect species andWolbachia transinfected inAedes mosquito species has formed the basis for biocontrol programs asWolbachia strains inhibit arboviral replication and can spread through populations. Resident strains in wild Culicine mosquito populations (the vectors of most arboviruses) requires further investigation given resident strains can also affect arboviral transmission. As Madagascar has a large diversity of both Culicine species and has had recent arboviral outbreaks, an entomology survey was undertaken, in five ecologically diverse sites, to determine theWolbachia prevalence. We detected diverse novel residentWolbachia strains within theAedeomyia, Culex, Ficalbia, Mansonia andUranotaenia genera.Wolbachia prevalence rates and strain characterisation through Sanger sequencing with multilocus sequence typing (MLST) and phylogenetic analysis revealed significant diversity and we detected co-infections with the environmentally acquired bacteriaAsaia . Mosquitoes were screened for major arboviruses to investigate if any evidence could be provided for their potential role in transmission and we report the presence of Rift Valley fever virus in threeCulex species:Culex tritaeniorhynchus, Culex antennatus andCulex decens . The implications of the presence of residentWolbachia strains are discussed and how the discovery of novel strains can be utilized for applications in the development of biocontrol strategies.